2011
DOI: 10.1057/abm.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of international environmental strategies of Korean firms: An explorative case-study approach

Abstract: The existence of negative externalities of businesses on the natural environment is widely accepted and firms are therefore pushed on various dimensions to be more environmentally responsible. In reaction, antecedents and determinants of corporate environmental strategies (CESs) have been identified that could support the internalisation of negative environmental impacts. However, these analyses often remain situated within a single industrialised-country context. They are therefore likely to not appropriately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Related to regulatory issues, the entrepreneurs mentioned several sustainabilityinhibiting issues the government could address. This is in line with previous studies, which have found that insufficient government support negatively influences the propensity of sustainability [42,43,46,47]. In addition, political support for sustainability, as affirmed by Bagas, can not only increase the entrepreneurs' motivations, but also enable the government to contribute to preserving natural and cultural heritage and ensuring appropriate infrastructures such as utilities, taxes, services, and regulations [22].…”
Section: Regulatory Barrierssupporting
confidence: 89%
See 1 more Smart Citation
“…Related to regulatory issues, the entrepreneurs mentioned several sustainabilityinhibiting issues the government could address. This is in line with previous studies, which have found that insufficient government support negatively influences the propensity of sustainability [42,43,46,47]. In addition, political support for sustainability, as affirmed by Bagas, can not only increase the entrepreneurs' motivations, but also enable the government to contribute to preserving natural and cultural heritage and ensuring appropriate infrastructures such as utilities, taxes, services, and regulations [22].…”
Section: Regulatory Barrierssupporting
confidence: 89%
“…As regulations and policies can create a part of social and environmental justice where each individual has the same rights to social and environmental progress, it is also important to include them in this study. Insufficient regulations and support from the government for environmental strategies are often found to be barriers to the transition to greater sustainability [42,43,46,47]. However, if better-developed (and this is ultimately reflected upon in the final part of this study), regulations and policies could also be considered to act as facilitators.…”
Section: Barriers To Achieving Sustainability Goals In Smesmentioning
confidence: 94%
“…In later studies, Elkington (1998) and Carter and Rogers (2008) specified that corporations play a primary role in promoting economic, ecological, and social responsibilities that are resulted from their actions at the different level of the supply chain. Since Asian countries have become outsourcing factories of the world, sustainability issues have been examined in different geographic settings such as the Corporate Social Responsibility (CSR) practices of several companies in China (Cooke & He, 2010;Jiang & Zhu, 2013) and Japan (Aman & Nguyen, 2012), the environmental responsibility of Korean firms (Cho & Voss, 2011), and Indian firms (Luthra et al, 2018). Social responsibility practices in the supply chain are defined as the perspectives of product and process that influence the safety, wellness and welfare of people (Carter, 2005;Carter & Easton, 2011).…”
Section: Sustainability and Supply Chain Social Responsibilitymentioning
confidence: 99%
“…There have been several studies linking a wide variety of concepts and tools within the extant field of EM ranging from EM and firm performance (Claver et al, 2007;Lopez-Gamero et al, 2009;Aragon-Correa et al, 2008;Vachon and Klassen, 2008), green supply chain management and EM systems (Zhu et al, 2008a,b;Walker et al, 2008;Adriana, 2009), waste management (Daian and Ozarska, 2009;Turan et al, 2009), environmental transformation and market orientation (Gonzalez-Benito and GonzalezBenito, 2010) to barriers to EM (Massoud et al, 2010;Shi et al, 2008), environmental behaviors of the firms (Liu, 2009;Liu and Ye, 2012) and human resources dimensions and EM (Jabbour and Santos, 2008). Moreover, mounting environmental concerns have also led to research on the implementation of CEP practices focusing on the antecedents and drivers of CEP (Christmann, 2004;Cho and Voss, 2011;Gonzalez-Benito andGonzalez-Benito, 2010, Tatoglu et al, 2014).…”
Section: Background Literature and The Conceptual Frameworkmentioning
confidence: 99%